Haploinsufficiency of the folliculin gene leads to impaired functions of lung fibroblasts in patients with Birt–Hogg–Dubé syndrome. Issue 21 (15th November 2016) - Hoshika, Yoshito; Takahashi, Fumiyuki; Togo, Shinsaku; Hashimoto, Muneaki; Nara, Takeshi; Kobayashi, Toshiyuki; Nurwidya, Fariz; Kataoka, Hideyuki; Kurihara, Masatoshi; Kobayashi, Etsuko; Ebana, Hiroki; Kikkawa, Mika; et al.
Abstract: Birt–Hogg–Dubé syndrome (BHDS) is an autosomal dominant inherited disorder caused by germline mutations in the FLCN gene, and characterized by skin fibrofolliculomas, multiple lung cysts, spontaneous pneumothorax, and renal neoplasms. Pulmonary manifestations frequently develop earlier than other organ involvements, prompting a diagnosis of BHDS. However, the mechanism of lung cyst formation and pathogenesis of pneumothorax have not yet been clarified. Fibroblasts were isolated from lung tissues obtained from patients with BHDS ( n = 12) and lung cancer ( n = 10) as controls. The functional abilities of these lung fibroblasts were evaluated by the tests for chemotaxis to fibronectin and three‐dimensional (3‐D) gel contraction. Fibroblasts from BHDS patients showed diminished chemotaxis as compared with fibroblasts from controls. Expression of fibronectin and TGF‐β1 was significantly reduced in BHDS fibroblasts when assessed by qPCR. Addition of TGF‐ β 1 in culture medium of BHDS lung fibroblasts significantly restored these cells' abilities of chemotaxis and gel contraction. Human fetal lung fibroblasts (HFL‐1) exhibited reduced chemotaxis and 3‐D gel contraction when FLCN expression was knocked down. To the contrary, a significant increase in chemotactic activity toward to fibronectin was demonstrated when wild‐type FLCN was overexpressed, whereas transduction of mutant FLCN showed no effect on chemotaxis. Our results suggest that FLCN is associated with chemotaxis in lung fibroblasts. Together with reduced TGF‐ β 1 expression by BHDS lung fibroblasts, a state of FLCN haploinsufficiency may cause lung fibroblast dysfunction, thereby impairing tissue repair. These may reveal one mechanism of lung cyst formation and pneumothorax in BHDS patients. Abstract : A state of FLCN haploinsufficiency may cause lung fibroblast dysfunction, thereby impairing tissue repair. These may reveal one mechanism of lung cyst formation and pneumothorax in BHDS patients.